2020
DOI: 10.3389/fimmu.2019.03017
|View full text |Cite
|
Sign up to set email alerts
|

Steroids, Pregnancy and Fetal Development

Abstract: Maternal glucocorticoids critically rise during pregnancy reaching up to a 20-fold increase of mid-pregnancy concentrations. Concurrently, another steroid hormone, progesterone, increases. Progesterone, which shows structural similarities to glucocorticoids, can bind the intracellular glucocorticoid receptor, although with lower affinity. Progesterone is essential for the establishment and continuation of pregnancy and it is generally acknowledged to promote maternal immune tolerance to fetal alloantigens thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 136 publications
2
92
0
2
Order By: Relevance
“…The RECOVERY trial, which demonstrated a mortality benefit of dexamethasone in patients with COVID-19 who required respiratory support, did include pregnant and breastfeeding patients and reported no pregnancy-associated adverse outcomes [ 37 ]. Use of high doses of dexamethasone in early pregnancy has been associated with poor pregnancy outcomes in mice, mares, and dogs [ 38 ]. These outcomes included early pregnancy termination, impaired fetal growth, and abnormal placentation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RECOVERY trial, which demonstrated a mortality benefit of dexamethasone in patients with COVID-19 who required respiratory support, did include pregnant and breastfeeding patients and reported no pregnancy-associated adverse outcomes [ 37 ]. Use of high doses of dexamethasone in early pregnancy has been associated with poor pregnancy outcomes in mice, mares, and dogs [ 38 ]. These outcomes included early pregnancy termination, impaired fetal growth, and abnormal placentation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of high doses of dexamethasone in early pregnancy has been associated with poor pregnancy outcomes in mice, mares, and dogs [ 38 ]. These outcomes included early pregnancy termination, impaired fetal growth, and abnormal placentation [ 38 ]. However, the RECOVERY trial utilized dexamethasone 6 mg daily, which is not high dose [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before the parturition process starts, a relaxation state of the myometrium with minimum sensitivity to stimulatory uterotonins, such as PGs, is controlled by progesterone ( Mesiano, 2004 ; Ilicic et al, 2020 ). Progesterone is a key player in the establishment and maintenance of pregnancy and its role and regulation have been extensively studied in human and experimental models ( Arck et al, 2007 ; Forde et al, 2009 ; Solano and Arck, 2020 ). Progesterone withdrawal usually indicates the initiation of the parturition process with changes in the contractile activity of the myometrium.…”
Section: Eicosanoidsmentioning
confidence: 99%
“…Irregular actions of these hormones may provide various causes of RIF. P 4 play critical roles for the establishment and maintenance of pregnancy by not only its endocrine but also immunological effects [14,15]. P 4 -PR transcriptional network along with estrogen signaling promotes spatiotemporal regulation of various target genes for achieving uterine receptivity in the uterus [16].…”
Section: Introductionmentioning
confidence: 99%